» Toward a relative chronology of the earliest Baltic and Slavic sound changes&#187 - Matasović, Ranko (Array, 2005)
This paper establishes the relative chronology of Balto-Slavic sound changes. It also discusses previous proposals by Frederik Kortlandt and others.